Career Services in Improving Career Decisions of Class XII MIPA 1 Students of MAN 2 Indramayu - Arinie Falhah; Syifa Nur Fadilah (Journal Of Psychology, Counseling And Education, 2026)
This study aims to determine the role of the career service program in improving career decisions of grade XII MIPA 1 students at MAN 2 Indramayu. It also examines the career services implemented at MAN 2 Indramayu and the role of career guidance and counseling services in improving career decisions among grade XII MIPA 1 students at MAN 2 Indramayu. This research is a descriptive qualitative study. The sources and types of data used are primary and secondary data. The data collection technique uses the first method of observation or digging for information, phenomena to be recorded; the second method is interviews, interviews here with guidance and counseling teachers and grade XII MIPA 1 students, and the third method is documentation study, this documentation study relates to documents from counselors/guidance and counseling teachers, MIPA 1 students, and photographs taken while in the field. The implementation of classical career guidance at MAN 2 Indramayu is considered effective in improving students' career decisions despite limited time and human resources, as evidenced by a 10.4% increase in students' career decisions who choose to continue to college from the previous two years. In the 2022–2023 academic year, it was 27.1%, then increased in the 2023–2024 academic year to 31.3%, and reached its highest figure in the 2024–2025 academic year at 41.7%. Counseling services are perceived as beneficial by students, but the Talent and Interest Assessment program is deemed inaccurate and needs to be evaluated to improve its relevance to student needs.